2015
DOI: 10.1136/jech-2014-204784
|View full text |Cite
|
Sign up to set email alerts
|

Male involvement and maternal health outcomes: systematic review and meta-analysis

Abstract: BackgroundThe developing world accounts for 99% of global maternal deaths. Men in developing countries are the chief decision-makers, determining women's access to maternal health services and influencing their health outcomes. At present, it is unclear whether involving men in maternal health can improve maternal outcomes. This systematic review and meta-analysis aimed to investigate the impact of male involvement on maternal health outcomes of women in developing countries.MethodsFour electronic databases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
324
3
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(378 citation statements)
references
References 60 publications
20
324
3
8
Order By: Relevance
“…These findings support studies that have identified the importance of addressing community norms, including involvement of faith-based and lay leaders, to address negative community attitudes and norms regarding critical MNCH behaviours (Campbell et al 2013;Crissman et al 2013;Pell et al 2013;Pharr et al 2016;Skovdal and Campbell 2010;Yargawa and Leonardi-Bee 2015). In particular, in Ghana's Northern region, Moyer et al (2014) concluded that community-based solutions, including working with community leaders, were needed in order to address challenges facing maternal and child health.…”
Section: Comparison Areasupporting
confidence: 63%
See 2 more Smart Citations
“…These findings support studies that have identified the importance of addressing community norms, including involvement of faith-based and lay leaders, to address negative community attitudes and norms regarding critical MNCH behaviours (Campbell et al 2013;Crissman et al 2013;Pell et al 2013;Pharr et al 2016;Skovdal and Campbell 2010;Yargawa and Leonardi-Bee 2015). In particular, in Ghana's Northern region, Moyer et al (2014) concluded that community-based solutions, including working with community leaders, were needed in order to address challenges facing maternal and child health.…”
Section: Comparison Areasupporting
confidence: 63%
“…A recent systematic review and meta-analysis indicated that interventions to involve male household decision-makers in maternal health activities, including ANC, was associated with improved utilisation of maternal health services and reduced odds of postpartum depression (Yargawa and Leonardi-Bee 2015). Additionally, Speizer, Story, and Singh (2014) demonstrated the positive effects of supportive community norms on institutional delivery in northern Ghana.…”
Section: Challenges For Antenatal Care In Sub-saharan Africamentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The World Health Organization has focused on accelerating the reduction of mortality related to pregnancy and childbirth and considered it as the first priority of its reproductive health program and believed that men are considered as key partners to improve maternal health and reduce mortality of them. [2] Men are the key players to influence reproductive health outcomes of their wives and children.…”
Section: Introductionmentioning
confidence: 99%
“…No cabe duda que la madre el hijo(a) y todo el proceso de parto puede verse beneficiado con la presencia y soporte de la pareja. La evidencia apoya esta práctica en algunos casos (67)(68)(69)(70), principalmente cuando el varón ha sido preparado para estar presente (71). Sin embargo, las recomendaciones de presencia activa del padre como acompañante se han focalizado en el beneficio para el proceso de parto.…”
Section: Demandas Paternas De Preparación Para El Nacimientounclassified